Let us consider the 7^{th} term as T_{7}

So,

T_{7} = T_{6+1}

= ^{10}C_{6} (3x^{2})^{10-6} (\( \dfrac{-1}{x^3}\))^{6}

= ^{10}C_{6} (3)^{4} (x)^{8} (\( \dfrac{1}{x^{18}}\))

= \(\dfrac{10×9×8×7×81}{ 4×3×2×x^{10}}\)

= \(\dfrac{ 17010 }{ x^{10}}\)

The 7^{th} term of the expression is \( \dfrac{ 17010 }{ x^{10}}\)

Find the term independent of x in the expansion of \( (\dfrac{3}{2x^2} – \dfrac{1}{3x})^9\)

Find the middle term in the expansion of \((x-\dfrac{ 1}{x})^{2n+1}\)

Find the middle term in the expansion of (1 + 3x + 3x^{2} + x^{3})^{2n}

Find the middle term in the expansion of (1 – 2x + x^{2})^{n}

Find the middle term in the expansion of \( (\dfrac{x}{a} – \dfrac{a}{x})^{10}\)